We have to solve : log(4) (x+4) + log(4) 1/(x+1) - 1 = 0

Use the relation log a + log b = log (a*b)

log(4) (x+4) + log(4) 1/(x+1) - 1 = 0

=> log(4) (x + 4) / (x + 1) - 1 = 0

=> log(4) (x...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

We have to solve : log(4) (x+4) + log(4) 1/(x+1) - 1 = 0

Use the relation log a + log b = log (a*b)

log(4) (x+4) + log(4) 1/(x+1) - 1 = 0

=> log(4) (x + 4) / (x + 1) - 1 = 0

=> log(4) (x + 4) / (x + 1) = 1

=> (x + 4) / (x + 1) = 4

=> x + 4 = 4(x + 1)

=> x + 4 = 4x + 4

=> 3x = 0

=> x = 0

**Log 4 and log 1 exist, so x = 0 is a valid solution.**